Karakteristik Pasien Amnesia Pasca Cedera Otak di Rumah Sakit Umum Daerah Provinsi Nusa Tenggara Barat - Lalu Wahyu Alfian Muharzami; Rohadi Muhammad Rosyidi; Ilsa Hunaifi; Bambang Priyanto (Faculty of Medicine Universitas Mataram, 2022)
Background: Traumatic Brain Injury (TBI) is a brain disorder caused by a traumatic process such as an impact, blow, or stab to the head, causing impaired brain function. Several external causes of TBI, such as falls, road traffic accidents, and beatings/assaults. Impaired memory function is one form of the neuropsychological disorder that can occur after injury. Post-Traumatic Amnesia (PTA) is a post-injury condition characterized by difficulty remembering things that were happened before or retaining information that has just happened. Methods: This research was conducted at West Nusa Tenggara Province General Hospital using a cross-sectional design and has passed the review of the research ethics team (ethical clearance). The number of research samples was 40 people with brain injury. We collected head CT scan results and interviews using the Galveston Orientation and Amnesia Test (TOAG) questionnaire. Sampling using a consecutive sampling method. Data are presented descriptively. Results: Of the 40 TBI patients, 33 patients had PTA (82.5%). Most patients with PTA are between 18 and 30 years of age (45.46%), most of them were male (81.8%), and most patients had high school educational levels (42.43%). Based on the severity of brain injury, most PTA patients had a mild brain injury (57.58%). Based on the head ct scan, most PTA patients had diffuse lesions (51.52%). Conclusion: TBI patients who experienced PTA were dominated by men aged 18 to 30 years and had a high school education level. In addition, the location of diffuse lesions is often seen in TBI patients with PTA.